Transformasi Pelayanan Mahasiswa: Menyemai Inspirasi Melalui Pastoral Legio Maria - Kami, Yoseph; Selatang, Fabianus (Perspektif, 2025)
This study will aim to look at the role played by the activities of the Legion of Mary towards the development of student ministry in the Pastoral Ministry Study Programme of STP-IPI. God created humans to depend on each other, and service is a tangible manifestation of mutual need. The spirit of proclamation, instilled by the good news and the sacrifice of Jesus, is the inspiration of the Church and everybody who is part and parcel of it; this encompasses students in the STP-IPI Pastoral Ministry Study Programme. Some factors, both intrinsic like personal interests and extrinsic like dependence on technology and pressure from academics, deny many of the students the opportunity to be actively involved in this service. Legion of Mary activities become a way of awakening and invigorating that spirit of service to Jesus in students. This research uses a quantitative method with an approach called quantitative description. The result shows that these activities hold an important role in forming students' services and are important in shaping characters and awareness of the importance of quality service.